(untitled) - Faivre-Tavignot, Bénédicte (Hoboken, NJ, 2016)
This book analyzes how social business and base of the pyramid approaches allow companies to reinvent themselves, or in other words how they are the levers for strategic renewal.
Keywords: Trách nhiệm xã hội của doanh nghiệp,Social responsibility of business